1998
DOI: 10.1006/jmre.1998.1428
|View full text |Cite
|
Sign up to set email alerts
|

Proton Diffusion andT1Relaxation in Polyacrylamide Gels: A Unified Approach Using Volume Averaging

Abstract: The structure of polyacrylamide gels was studied using proton spin-lattice relaxation and PFG diffusion methods. Polyacrylamide gels, with total polymer concentrations ranging from 0.25 to 0.35 g/ml and crosslinker concentrations from 0 to 10% by weight, were studied. The data showed no effect of the crosslinker concentration on the diffusion of water molecules. The Ogston-Morris and Mackie-Meares models fit the general trends observed for water diffusion in gels. The diffusion coefficients from the volume ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 68 publications
4
22
0
Order By: Relevance
“…Mathematical models, based on the volume averaging method, that simulate the effects of multiphase transport on the diffusion coefficient and spin-lattice relaxation constant, have previously been derived and compared with NMR data. 23,37 A detailed analysis of the effects of compartmentalization on signal decay associated with T 2 relaxation and diffusion is beyond the scope of this paper, but will be the topic of future work.…”
Section: Discussionmentioning
confidence: 98%
“…Mathematical models, based on the volume averaging method, that simulate the effects of multiphase transport on the diffusion coefficient and spin-lattice relaxation constant, have previously been derived and compared with NMR data. 23,37 A detailed analysis of the effects of compartmentalization on signal decay associated with T 2 relaxation and diffusion is beyond the scope of this paper, but will be the topic of future work.…”
Section: Discussionmentioning
confidence: 98%
“…In polymer gels, Penke et al observed a different situation (12). At equivalent monomer concentrations, water diffusion in polyacrylamide gels was significantly slower than in acrylamide solutions (a 50% decrease at concentrations of 0.3 g ml −1 ).…”
Section: Solvent Dynamics and Sol-gel Transitionmentioning
confidence: 96%
“…The simplest way to calculate the consequences of these effects on diffusion is to use the general effective medium theories developed for heterogeneous media. Several effective medium models for transport properties, differing in the way averaging is performed over the different phases, have been applied to colloidal suspensions and polymer gels (1,12,13,(34)(35)(36)(37)(38). The basic theory is that of Maxwell, who treated the case of the generalized conductivity of a dilute suspension of non-interacting spherical particles.…”
Section: Effective Medium Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…where D is the proton diffusion coefficient in the gel [37]. The continuous partial differential equation (PDE) of the Fick's second law was replaced with a discrete approximation.…”
Section: Simulations Of Proton Diffusion Kineticsmentioning
confidence: 99%